Some New Results of Weaving K-Frames in Hilbert Spaces. (21st May 2021) - Xiang, Zhong-Qi
Abstract: In this article, we first provide some sufficient conditions, and necessary and sufficient conditions for K -woven frames to be preserved under a bounded linear operator and particularly, we report that applying two different operators to K -woven frames can leave them K -woven. Several new methods on the construction of K -woven frames are also presented. Finally we show that the perturbation condition involved in one known result on K -woven frames can have a wider choice for the corresponding K -frames.